Study on the flame retardancy of nano-Sb2O3/BPS-PBT composites. (25th July 2019) - Xu, Jianlin; Ma, Bingxue; Niu, Lei; Xu, Chengcheng; Chen, Zhou; Lin, Yonggang
To improve the flame retardancy of polybutylene terephthalate (PBT), PBT-based flame retardant composites containing antimony trioxide nanoparticles (nano-Sb2 O3 ) and brominated polystyrene (BPS) were investigated. Nano-Sb2 O3, BPS, and PBT were dispersed by ball milling method to obtain composite powders, and the nano-Sb2 O3 /BPS-PBT samples were prepared by melt blending and injection molding methods. The flame retardancy of nano-Sb2 O3 /BPS-PBT composites was investigated. The results showed that nano-Sbs2 O3 can obviously improve the flame retardancy of PBT-based composites. When the nano-Sb2 O3 /BPS-PBT composite contains nano-Sb2 O3 with 5 wt% of mass fraction and BPS with 10 wt% of mass fraction, the nano-Sb2 O3 /BPS-PBT composite has excellent flame retardancy, in which the UL94 degree of flame retardancy achieves V-0 grade and the limit oxygen index is 28.3%.